2020
DOI: 10.1017/jfm.2020.940
|View full text |Cite
|
Sign up to set email alerts
|

Non-modal transient growth of disturbances in pulsatile and oscillatory pipe flows

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 31 publications
9
34
0
Order By: Relevance
“…The fact that different geometric disturbances can trigger different structures is consistent with the non-modal stability analysis of Xu et al. [ 20 ]. The analysis showed that the instantaneous Sexl–Womersley profile is linearly unstable (in the quasi-steady limit) during most of the DC phase.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The fact that different geometric disturbances can trigger different structures is consistent with the non-modal stability analysis of Xu et al. [ 20 ]. The analysis showed that the instantaneous Sexl–Womersley profile is linearly unstable (in the quasi-steady limit) during most of the DC phase.…”
Section: Resultssupporting
confidence: 86%
“…Next, we followed Xu et al. [ 20 ] and performed a linear non-modal stability analysis to identify the optimal perturbation for the parameter values of interest ( , , and several A ). This method produces the geometry (radial shape and axial/azimuthal wavenumbers) and the initial time ( ) of the perturbation achieving the maximum energy amplification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary nonlinear simulations further verified that triggering by these mechanisms can yield subcritical transition to turbulence. A similar technique has been applied in a recent study by Xu, Song & Avila (2021) for oscillatory and pulsating pipe flow. Among others, they have reported that pulsating pipe flows are generally dominated by helical perturbations.…”
Section: Introductionmentioning
confidence: 99%